The soccer goalkeeper profile: bibliographic review - Perez-Arroniz, M.; Calleja-González, J.; Zabala-Lili, J.; Zubillaga, A. (The Physician and Sportsmedicine, 2023)
Objective The main aim of this article was to review the existing scientific literature on the soccer goalkeeper.